2019
DOI: 10.4103/sjg.sjg_390_18
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation and pancreatic cancer: An updated review

Abstract: Pancreatic cancer is a devastating disease with poor prognosis in the modern era. Inflammatory processes have emerged as key mediators of pancreatic cancer development and progression. Recently, studies have been carried out to investigate the underlying mechanisms that contribute to tumorigenesis induced by inflammation. In this review, the role of inflammation in the initiation and progression of pancreatic cancer is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 188 publications
0
63
0
Order By: Relevance
“…Furthermore, CCR3, CCR4, CCR5 and CCR8 were also found to be associated with viral carcinogenesis, a greater number of CCR genes than those identified to be concerned with carcinogenesis in previous studies (23,6568). Since various studies have shown its close association with inflammation and immunity (6975), this is highly relevant to PDAC. Also, considering the function of CCR genes in mediating inflammation, and that CCR5, CCR6 and CCR9 were significantly associated with the overall survival of patients with early-stage PDAC (as indicated by the results of survival analysis), it was concluded that CCR5, CCR6 and CCR9 serve important roles in the development and progression of PDAC.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, CCR3, CCR4, CCR5 and CCR8 were also found to be associated with viral carcinogenesis, a greater number of CCR genes than those identified to be concerned with carcinogenesis in previous studies (23,6568). Since various studies have shown its close association with inflammation and immunity (6975), this is highly relevant to PDAC. Also, considering the function of CCR genes in mediating inflammation, and that CCR5, CCR6 and CCR9 were significantly associated with the overall survival of patients with early-stage PDAC (as indicated by the results of survival analysis), it was concluded that CCR5, CCR6 and CCR9 serve important roles in the development and progression of PDAC.…”
Section: Discussionmentioning
confidence: 99%
“…[ 17 ] TNF-a is known to induce activation of NF-κB , a transcription factor, to convert tumor suppressors to tumor promotors and substances such as IL-6 to induce pancreatic intraepithelial neoplasia. [ 18 ] In a previous nationwide population-based cohort study of the association between candidiasis and cancer, there was a significant association between candidiasis groups and pancreatic cancer. The association in this study was attributed as surveillance bias, but the association has been reported in various studies.…”
Section: Discussionmentioning
confidence: 99%
“…We are aware of that our proteomic analysis is a snapshot of established PDAC cases, and the propose bacteria-induced carcinogenesis model for the biliary tract is still speculative, not validated, and therefore must be interpreted with caution ( Figure 3 ). The model initiates with unique or multiple dysbiotic factors that promote repeated inflammatory events ( 80 ), classically described as stones in the biliary tract, tobacco use, obesity, diabetes mellitus or genetic factors ( 81 ). Those promoting factors change the usual biliary tract bacteria composition expected for that individual, shaped according to diet, genetic background, sex, race, age, etc.…”
Section: Discussionmentioning
confidence: 99%